Internationalization strategy: how can Nova School of Business and Economics attract Canadian students? - Ferreira, Teresa Mendes Cortês (2016)
Internationalization is becoming an essential factor for today’s society, determinant for the development not only for individuals but also for Higher Education Institutions. This dissertation aims to advise Nova SBE on how to attract Canadian students. It will also help to understand the current trends and students’ behaviors on studying abroad and based on that provide different. For this to become possible, it was developed a qualitative research in order to understand the main insights on what makes Canadian students to study abroad. The biggest obstacle for students studying abroad is the lack of financial funds, which makes scholarships a requirement for students to consider this possibility. In what concerns the study of Nova SBE, it was mentioned that there is a lack of attention and care by the faculty staff in order to help the students integrate in the university and the city.